Application of Collaboration Model in Improving Students' Learning Outcomes in Indonesian Language Subjects in Grade IV of Elementary Schools - Nur Kalifah, Diah Rizki; Agustina, Elisa; Qiftiyah, Maratul (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2024)
The purpose of the study was to determine the application of the collaboration model in improving student learning outcomes in Indonesian language subjects in Grade IV of Elementary School. The research method used was classroom action research (CAR). The research design adopted the Kemmis and Taggart model which consisted of two cycles, each cycle consisting of four stages, namely planning, implementation, observation and reflection. The subjects of the study were 26 grade IV elementary school students. Data collection through observation and interviews. Data analysis in this study used qualitative data analysis, namely with statistical models such as tables and diagrams from the results of observations and values ​​​​of each cycle and using quantitative data analysis by comparing data obtained from the implementation of cycle I and cycle II activities. The results of the study showed an increase in learning outcomes after the implementation of the collaboration model in Indonesian language subjects which was proven by the average value of cycle I obtained 70.77 with a percentage of 69.23% in cycle I students who completed 18 students while in cycle II obtained an average value of 82.69 with a percentage of 100% and students who completed 26 students. So it can be concluded that from cycle I and cycle II there was an increase in learning outcomes after the implementation of the collaboration model.